Combination of small molecule inhibitor interacting with PD-1/PD-L1 and anti-PD-1 antibody for use in treatment of cancer - ZHANG NONG; WANG FEILAN; WANG YUGUANG (2021)
The invention provides a method of treating cancer. The method comprises the steps of administering a subject in need a therapeutically effective amount of a small molecule inhibitor interacting withPD-1/PD-L1, a pharmaceutically acceptable salt or prodrug thereof, and a therapeutically effective amount of an anti-PD1 antibody, wherein the small molecule inhibitor interacting with PD-1/PD-L1 is not a protein. 本发明提供了治疗癌症的方法，其包括向有需要的受试者施用治疗有效量的PD-1/PD-L1相互作用的小分子抑制剂、其药学上可接受的盐或其前药，和治疗有效量的抗PD-1抗体，其中，所述PD-1/PD-L1相互作用的小分子抑制剂不是蛋白质。